Superiority and Mimicry in Korea Reomit - Sumekar Tanjung (International Journal of Media and Communication Research (IJMCR), 2022)
This study aims to describe the hegemonic relationship between Jang Hansol and the other who initiate superiority and mimicry issues on the Korea Reomit channel. Jang Hansol's popularity clearly complements the hegemonic discourse of Korean colonialism in Indonesia, as obviously seen in the form of hybrid culture. The importance of this research lies in the absence of previous studies that examined the relationship between the colonized and the colonizer on YouTube. The researcher sees the presence of binary opposition between Jang Hansol and three content creators who play a role in their respective areas of subordination. This study uses a qualitative descriptive method by dissected three collaborative videos between Jang Hansol and Jerome Polin Sijabat, Alphiandi, and Natya Shina. It is readily apparent that the three videos serve as Jang Hansol's colonial strategy in maintaining his power as the superior while at the same time subjugating the position of the colonized. The findings show two hegemonic relations. First, the hierarchical relation shows that the colonizer expresses speech through native languages to strengthen his position as superior. Second, conflicting relations of the other show that the attempts to imitate the colonizer only produce imperfect imitation. These two relations show the Korean hegemony that has been built between Jang Hansol and the other along the surgin Korean Wave.